Faktor-Faktor yang Mempengaruhi Prilaku Pemberian Asi Eksklusif di Kelurahan Tabona Kecamatan Kota Ternate Selatan - Soamole, Karima (UPPM Politeknik Kesehatan Kemenkes Ternate, Maluku Utara, Indonesia, 2014)
Abstract : It is estimated that 80% of mothers who gave birth were able to produce milk in quantities sufficient for the purposes of the baby in full without any additional food and according to the World Health Organization recommends breastfeeding until the age of 4-6 months baby. Annually, more than 25,000 babies Indonesia and 1.3 million babies around the world can be saved by exclusive breastfeeding in 1999, while according to the 2000 report, the WHO approximately 1.5 million children die because they are not feeding properly, less than 15% infants worldwide are given for four months of exclusive breastfeeding and complementary feeding is often inappropriate and unsafe. This research is explanatory research because it explains the relationship between independent variables and dependent variable through hypothesis testing. The method used in this study is a survey method with cross sectional study design. The population in this study are all mothers who breastfeed in Puskesmas Kalumata 2012. Knowledge of the highest in the category of knowledge of both 81 (95.3%) and the behavior of the Exclusive breastfeeding is highest among respondents with a good knowledge of the 55 categories (67.9%). Respondents' attitudes toward breastfeeding Exclusive showed much respondeng that supports 54 (63.5%) and 31 (36.5%) that does not support exclusive breastfeeding her baby. Family Support tehadap respondents in the most exclusive breastfeeding: supporting respondents in exclusive breastfeeding her baby 64 (75.3%) and 21 (24.7%) who did not support the.